Sport governance and community empowerment: Insights from an international systematic review - Sulistiyowati, Tutut Bina; Juwono, Vishnu; Thamrin, Muhammad Husni (Edelweiss Applied Science and Technology, 2026)
Sport governance has a significant impact on community development at three levels: local, national, and global. The change of the paradigm in governance sets transparency, participation, accountability, and collaboration among stakeholders as the cornerstones for sport to effectively strengthen the community. The purpose of this study is to present a systematic literature review (SLR) of international studies conducted over the last two decades investigating the nexus between sport governance and community empowerment. The existing literature on governmentality in sports remains fragmented and requires systematic integration. The SLR follows the PRISMA protocol and includes publications indexed in Scopus and Web of Science between 2006 and 2025. The study identified different governance structures that enable communities to have power and contribute to community development, as well as drivers and barriers to the implementation of inclusive governance principles. In conclusion, the study demonstrates that sustainable and transformative sport governance for community empowerment ultimately depends on the integration of participatory, context-specific, and multi-sectoral approaches supported by robust collaborative practices. These insights offer practical guidance for policymakers, sport organizations, and researchers in advancing sport-based community development and refining governance frameworks.